EFL Teacher Experiences in Developing Writing Proficiency for Scientific Journal Publication Through Extensive Reading - Daviq Rizal; Resti Farikhah Zulaefa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research investigated how EFL teachers become more engaged with extensive reading when developing their writing proficiency. This research used a narrative inquiry method to collect data on individuals who have and have not engaged in extensive reading. An initial questionnaire was sent to EFL teachers through Google-form. Fifteen EFL high school teachers responded to the questionnaire, most female and 33 years old. Afterward, one chosen EFL teacher was interviewed to discuss how they use extensive reading to improve their writing skills. The results found that the keys to improving scientific article writing as a hobby are that English teachers read articles from various sources to gain more information and understand different perspectives. Besides, they set a reading target of 15 minutes per day for them, leading to 20 books per year, or at least they can start practicing extensive reading since university. Also, reading fairytales, comics, folktales, magazines, novels, and short stories as extensive reading materials could increase their writing proficiency. In brief, extensive reading improves vocabulary mastery, reading fluency, and English proficiency, helping teachers better convey ideas and thoughts through written language. The implication was also discussed here.